THE DEVELOPMENT OF ONLINE LEARNING USING PROBLEM BASE (PBL) ON GENERAL APPLICATIONS OF STATISTICS IN HYPOTHESIS TESTING FOR UNDERGRADUATE STUDENTS - ศิลาอาศน์, พงษ์นที (Pathumthani University Academic Journal, 2020)
This research is a research and education development that has objectives 1) to develop and find the effectiveness of online lessons by using Online Learning Using Problem Base (PBL) such as: General Applications of Statistics in Hypothesis Testing for Undergraduate Students who have effectiveness in accordance with E1 / E2 = 80/80, 2) to study the effectiveness index of Online Learning Using Problem Base (PBL) on General Applications of Statistics in Hypothesis Testing 3) to study the satisfaction of learners with online lesson by using Online Learning Using Problem Base (PBL) on General Applications of Statistics in Hypothesis Testing for Undergraduate Students. The population who has been used in this research is the year 2nd undergraduate students of Rambhai Barni Rajabhat University who has enrolled General Applications of Statistics in Hypothesis in academic year 2/2018. The sample group which has been nominated randomly (Cluster Sampling) by using study groups units as a unit for random that get a class for sample group. The tools in this case stud are consisted of 1) Online Learning Using Problem Base (PBL) on General Applications of Statistics in Hypothesis Testing 2) Before and after learning achievement assessment 3) Satisfaction questionnaires. The results found that: 1) Development online lessons using Online Learning Using Problem Base (PBL) on General Applications of Statistics in Hypothesis Testing for Undergraduate Students who have effectiveness in accordance with E1/E2 82.17/81.00 in accordance with the specified standard, 2) The effectiveness index of Online Learning Using Problem Base (PBL) on General Applications of Statistics in Hypothesis Testing is .80 or 80.11 percent, 3) Students who has studied from online lessons by using Online Learning Using Problem Base (PBL) on General Applications of Statistics in Hypothesis Testing for Undergraduate Students have the high satisfaction with an average of 4.46 and a standard deviation in .52.